Método solvotérmico assistido por micro-ondas aplicado à obtenção de nanocristais de ITO : deposição e caracterização de filmes de ITO - Oliveira, Fernando Modesto Borges de (2012)
The formation of In1-xSnxO2 (ITO) nanocrystals through the conversion of radiant energy into heat has been studied by using an adapted domestic microwave oven. The formation of powder was obtained by heating the oven to 200 C using a heating rate of 50 C/min and soaking time of 30 min. The obtained powder by this method was characterized by X-ray Diffraction (XRD), Field Emission Scanning Electron Microscope (FEG-SEM), High Resolution Transmission Electron Microscope (HRTEM) and Selected Area Diffraction technique whose enable to distinguish possible crystalline phases, as well as the structure and morphology of the powder. Spherical particles with average size of 4, 8 and 12 nm were identified. This powder was characterized by sensing response against the presence or absence of oxygen gas. Finally, ITO powder was deposited on amorphous quartz or glass substrates by spin coating method. The films thus obtained were characterized by FEG-SEM, UVVIS and the electrical sheet resistance was measured using a four probe tips. Best results were obtained in the film whose particles were synthesized at pH 6,5. Optical transmittance at visible region of 98,5 % was observed and with an optical gap and resistance calculated to be 3,55 eV and 3,6.10-3 Ω.m respectively.